Malignant melanoma arising in congenital melanocytic nevi: clinical and dermoscopic challenges - Fatma Pelin Cengiz; Nazan Emiroglu; Anil Gulsel Bahali; Ozlem Su; Nahide Onsun (Our Dermatology Online, 2017)
Congenital melanocytic nevi (CMN) are visible pigmented lesions in the skin that are present at birth. CMN are benign malformations resulting from defective development of melanocyte precursors in the embryo. Six MMs from six patients were analyzed by clinical and dermoscopic examination. Of the patients, 33.3% were female (N = 2) and 66.6% were male (N = 4). Of the MMs, four (66.6%) were superficial spreading MM and two (33.3 %) were in situ MM. A reticular pattern was present in the MMs of three patients (50%), a homogeneous pattern was present in the other patients (50%) at the base of the MMs. Superficial spreading melanomas and in situ melanomas with atypical dots and globules and a blue-white veil were the most common dermoscopic features of MMs found in CMN.